Full-scale tests on masonry vaults strengthened with Steel Reinforced Grout. (15th May 2018) - De Santis, Stefano; Roscini, Francesca; de Felice, Gianmarco
Abstract: Masonry vaults can be particularly vulnerable against unsymmetrical service loads, support displacements and seismic actions. Retrofitting is often needed to ensure an adequate safety level according to current standard codes. Externally bonded composites are emerging as a possible retrofitting technique, but no experimental evidence is still available on the response of reinforced vaults taking into account the contribution of buttresses and backfill. This paper describes an experimental investigation on four full-scale vault specimens. One of them was tested unreinforced, whereas the other ones were strengthened with Steel Reinforced Grout (SRG), comprising ultra high tensile strength steel cords, bonded with lime-based mortar either to the extrados or to the intrados. The vaults were subjected to cyclic loading at 1/3 span. The backfill was visible through a panel of Plexiglas, allowing for the use of Digital Image Correlation to measure the displacement field and derive information on damage pattern and arch-fill interaction. Tests showed that SRG prevented the development of the four-hinge mechanism and avoided damage concentrations, increasing the deflection capacity and the strength of the arch by 2–3 times. Finally, it is shown that a simplified analytical approach based on limit analysis provides a reliable estimate of experimental load carrying capacity.